A Novel Mouse Model of iNKT Cell-deficiency Generated by CRISPR/Cas9 Reveals a Pathogenic Role of iNKT Cells in Metabolic Disease. Issue 1 (December 2017) - Ren, Yue; Sekine-Kondo, Etsuko; Shibata, Risa; Kato-Itoh, Megumi; Umino, Ayumi; Yanagida, Ayaka; Satoh, Masashi; Inoue, Komaki; Yamaguchi, Tomoyuki; Mochida, Keiichi; Nakae, Susumu; Kaer, Luc; et al.
Abstract iNKT cells play important roles in immune regulation by bridging the innate and acquired immune systems. The functions of iNKT cells have been investigated in mice lacking theTraj18 gene segment that were generated by traditional embryonic stem cell technology, but these animals contain a biased T cell receptor (TCR) repertoire that might affect immune responses. To circumvent this confounding factor, we have generated a new strain of iNKT cell-deficient mice by deleting theTraj18 locus using CRISPR/Cas9 technology, and these animals contain an unbiased TCR repertoire. We employed these mice to investigate the contribution of iNKT cells to metabolic disease and found a pathogenic role of these cells in obesity-associated insulin-resistance. The newTraj18 -deficient mouse strain will assist in studies of iNKT cell biology.